2015
DOI: 10.2337/db14-1329
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Specific Expression of Dominant-Negative Transcription Factor 7-Like 2 Causes Progressive Impairment in Glucose Homeostasis

Abstract: Investigations on the metabolic role of the Wnt signaling pathway and hepatic transcription factor 7-like 2 (TCF7L2) have generated opposing views. While some studies demonstrated a repressive effect of TCF7L2 on hepatic gluconeogenesis, a recent study using liver-specific Tcf7l2 2/2 mice suggested the opposite. As a consequence of redundant and bidirectional actions of transcription factor (TCF) molecules and other complexities of the Wnt pathway, knockout of a single Wnt pathway component may not effectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 53 publications
(91 reference statements)
5
68
0
Order By: Relevance
“…The possession of HA-tagged adenovirus vehicles for wild type TCF7L2 and TCF7L2DN 16 allowed us to assess the effect of their expression on 3T3-L1 differentiation (Figure 3c). Figure 3d shows that 48 h after the virus infection in 3T3-L1 cells, we were able to detect the expression of HA-tagged exogenous TCF7L2 or TCF7L2DN.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The possession of HA-tagged adenovirus vehicles for wild type TCF7L2 and TCF7L2DN 16 allowed us to assess the effect of their expression on 3T3-L1 differentiation (Figure 3c). Figure 3d shows that 48 h after the virus infection in 3T3-L1 cells, we were able to detect the expression of HA-tagged exogenous TCF7L2 or TCF7L2DN.…”
Section: Resultsmentioning
confidence: 99%
“…The generation of Ad-TCF7L2, Ad-TCF7L2DN and miR-17 over-expression plasmid has been previously presented. 16, 47, 48 miR-17 lentivirus construct was generated by inserting two copies of miR-17 precursor into the plv vector (Biosettia, CA, USA). RNA extraction and real-time PCR were performed as previously described, 16 with actin or U6 as the correspondent normalization controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…52,53 However, subsequent studies have found that TCF7L2 principally functions as a regulator of insulin action in liver and possibly other tissues. 54,55 This is important, as overall most SNPs associated with T2D are thought to principally have a role in beta cell dysfunction and very few SNPs have been found in genes that control insulin action in tissue such as muscle. As we observed β-catenin to be a major regulatory node in a GEM associated with IR we speculate that this pathway may represent a major biomarker for defects in insulin action.…”
Section: Discussionmentioning
confidence: 99%
“…In response to oxidative stress, β-catenins also directly interact with FOXO1 to increase its transcriptional activity (Almeida et al, 2007, Essers et al, 2005). Such β-catenin/FOXO1 interactions in liver have been shown to contribute to regulation of gluconeogenic gene expression and glucose homeostasis (Ip et al, 2015). …”
Section: Nuclear Receptors As a Paradigm For Affecting Insulin Actionmentioning
confidence: 99%